2004
DOI: 10.1111/j.1083-4389.2004.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Helicobacter pylori Infection and Dietary Iron Deficiency on Host Iron Homeostasis: A Study in Mice

Abstract: Infection with H. pylori did not cause iron deficiency in iron-replete mice. However, diminished iron stores in mice as a result of limited dietary iron intake were further lowered by concurrent infection, thus indicating that H. pylori competes successfully with the host for available iron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
3
17
0
Order By: Relevance
“…In a previous study that evaluated the effect of low dietary iron (8ppm Fe) in both male and female C57BL/6 mice after 30 weeks of H . pylori infection, mice on the low iron diet had lower serum iron, transferrin saturation, and hemoglobin than uninfected controls on low iron diet [51]. The results of the current study corroborated many of these findings, and extended analysis to a chronic timepoint of 12 months postinfection.…”
Section: Discussionsupporting
confidence: 81%
“…In a previous study that evaluated the effect of low dietary iron (8ppm Fe) in both male and female C57BL/6 mice after 30 weeks of H . pylori infection, mice on the low iron diet had lower serum iron, transferrin saturation, and hemoglobin than uninfected controls on low iron diet [51]. The results of the current study corroborated many of these findings, and extended analysis to a chronic timepoint of 12 months postinfection.…”
Section: Discussionsupporting
confidence: 81%
“…H. pylori could cause iron deficiency indirectly by suppressing gastric acid secretion, thereby reducing solubilization and uptake of dietary iron. There is also evidence obtained with a mouse infection model suggesting that H. pylori successfully competes for dietary iron when the diet is iron poor (20). Furthermore, a recent study showed that clinical isolates of H. pylori from patients with iron-deficiency anemia have higher rates of inorganic iron uptake than strains from patients with non-irondeficiency anemia (39).…”
mentioning
confidence: 99%
“…Previous studies in rodent models have reached inconsistent conclusions about the capacity of H. pylori to cause anemia (19)(20)(21)(22). The inconsistent conclusions might reflect the use of different H. pylori strains, differences in animal models, differences in diets, or differences in the time points selected for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies examining a potential link between H. pylori infection and anemia have also yielded conflicting results (19)(20)(21)(22). In one study, H. pylori-infected male INS-GAS mice (which overexpress gastrin) exhibited reductions in both hemoglobin and serum ferritin levels compared to uninfected animals; however, the mean corpuscular volume (MCV; a measure of the average size of erythrocytes) was elevated in the infected cohort (21), a finding that differs from the reduced MCV typically observed in patients with IDA.…”
mentioning
confidence: 99%